In Vivo Characterization of Cortical Noradrenergic Activity During Motor Learning Using an Optical Noradrenaline Sensor in Mice - Jones, Nathaniel (Université d'Ottawa / University of Ottawa, 2020)
The locus coeruleus (LC) projects ubiquitously to the cortex, and noradrenaline (NA) exerts powerful neuromodulatory control on cortical excitation and inhibition. Previous work has shown that NA plays an important role in motor processes, and further posits that dysregulation in NA function could be one of the culprits of motor-related deficits in many neurodevelopmental disorders, including Autism Spectrum Disorder. In order to characterize the change in NA levels during motor learning in awake and behaving mice, I employed a newly developed optical NA sensor, combined with in vivo two-photon imaging, to visualize spatiotemporal activation patterns of NA in the motor cortex. This experimental approach allows us to track and chronically image the same region of the motor cortex over multiple days, thus permitting the characterization of NA activity throughout the entirety of the motor learning process. I found that NA levels increase significantly during the initial phase of learning, which coincides with the structural and functional plastic changes that have been previously reported in the motor cortex during early stages of motor learning. The NA activity returns to baseline levels as the mice develop their movement strategy; however, the regions of NA release become more spatially clustered during the learning process. The results reported in this thesis provide a novel glimpse into the dynamics of NA activity in the motor cortex during motor learning, and it will provide new direction for the development of therapeutic strategies and diagnostic criteria for motor-related dysfunction in neurodevelopmental diseases.
Keywords: Noradrenaline; Motor Learning; Primary Motor Cortex; Two-Photon Imaging; ASD; NE1m